International education and student preferences: A focus on Kyrgyzstan - Enterieva, Mirgul (Journal of International Students, 2025)
The research aims to identify the reasons why international students choose Kyrgyzstan for their education, the challenges they may face, and their future expectations. A qualitative research method was used in the study, and 30 international students participated. The results of the study reveal that students choose Kyrgyzstan for education due to factors such as the opportunity to receive comparatively good education, affordable accommodation, food, etc., free education, scholarship opportunities, and the availability of education in languages they are familiar with. Additionally, students expressed the intention to return to their home countries and secure employment after completing their studies. Although most students face challenges, particularly in terms of language, they are generally satisfied with the education they receive. Based on the findings, some recommendations are provided in the study.